A Karakteristik Pengunjung Obyek Wisata Di Kawasan Danau Rawa Pening (Kasus Kecamatan Banyubiru, Kabupaten Semarang, Jawa Tengah) - Deasyka Milna Syahputri (Geography Education Study Program, Universitas Kanjuruhan Malang, 2019)
Abstract More comprehensive plan is needed in order to utilize natural resources as ecotourism development in the perspective of tourism society based, both in the provision of supporting facilities for tourism, the government cooperations and the private sector, also the society based on its potencial. So that the area became an attractive tourist destination. This research aims to find out the characteristics of tourists at Rawa Pening Lake. This research used descriptive quantitative method, the population of this study were the visitors of tourism objects around Rawa Pening, by using a sampling technique, produced 345 research respondents. The results show the characteristics of tourists on tourism objects in the Rawa Pening area. The knowledge of these characteristics can maximize the packaging and embodiment of facilities as supporting factors,include transportation services, accommodation, restaurants, shopping centers, networks banking, security facilities, and the other public facilities provided by tourism stakeholders to support all the tourism activities.